2008
DOI: 10.1186/1749-8104-3-9
|View full text |Cite
|
Sign up to set email alerts
|

Brain asymmetry is encoded at the level of axon terminal morphology

Abstract: Background: Functional lateralization is a conserved feature of the central nervous system (CNS). However, underlying left-right asymmetries within neural circuitry and the mechanisms by which they develop are poorly described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
141
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(158 citation statements)
references
References 35 publications
9
141
2
Order By: Relevance
“…3P). This asymmetrical expression of tac3a in the habenula is consistent with previous findings that the habenula in zebrafish displayed left-right asymmetries in gene expression (18,19). Interestingly, it was shown that neurons appear sooner in the left than in the right habenula (20).…”
Section: Localization Of Embryonic Tac3asupporting
confidence: 80%
“…3P). This asymmetrical expression of tac3a in the habenula is consistent with previous findings that the habenula in zebrafish displayed left-right asymmetries in gene expression (18,19). Interestingly, it was shown that neurons appear sooner in the left than in the right habenula (20).…”
Section: Localization Of Embryonic Tac3asupporting
confidence: 80%
“…In zebrafish larvae, efferent connectivity from left and right habenular nuclei forms distinct and segregated ring-shaped domains within dorsal and ventral regions of the IPN, respectively (figure 1a(vi),(vii); Aizawa et al 2005;Gamse et al 2005;Bianco et al 2008). A similar pattern of habenular efferent connectivity is observed in the larval IPN of medaka (see figure 1b (vi),(vii); Carl et al 2007).…”
Section: Results (A)supporting
confidence: 50%
“…The red arrowhead points to a neuropil domain that is detected exclusively in the left habenula of medaka. efferents are segregated along the dorsoventral axis of the interpeduncular nucleus (IPN) in the ventral midbrain (Aizawa et al 2005;Gamse et al 2005;Bianco et al 2008). Three main aspects are important to highlight about the development of epithalamic asymmetries.…”
Section: Introductionmentioning
confidence: 99%
“…These asymmetries are PpO-independent in the three species, although by different ontogenic mechanisms: (i) catsharks do not form a recognizable PpO [22], (ii) lampreys do have a midline PpO, but habenular asymmetries develop before the PpO is formed [22] and (iii) zebrafish have an asymmetrically positioned PpO but a sub-type of habenular asymmetries develops even in the absence of PpO, i.e. when the PpO is physically ablated [40,41,52]. In zebrafish, PpO-independent asymmetries of the Hb are very subtle and are frequently masked by the second type of epithalamic asymmetry, which is more conspicuous and dependent on the PpO (figure 4).…”
Section: Nodal As Laterality Modulator In Midlineunpaired Structuresmentioning
confidence: 99%
“…This first morphological asymmetry of the zebrafish epithalamus is followed by the development of prominent structural and functional asymmetries of the Hb ( figure 4a(v-viii)) [40,42]. Experiments of PpO ablation and mutant conditions that delay the onset of PpO asymmetric translocation reveal a requirement of an asymmetrically positioned PpO for the subsequent development of a sub-type of asymmetries in the Hb ( figure 4a(iii)) [40][41][42]58]. These asymmetries result from L-R differences in cell fate decisions towards two main neuronal identities, and it is possible that the PpO modulates these fate decisions as well as the timing of asymmetric habenular neurogenesis by acting on the Notch and Wnt signalling pathways [43,44].…”
Section: Nodal As Laterality Modulator In Midlineunpaired Structuresmentioning
confidence: 99%